1997
DOI: 10.1021/ja962929i
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Rate Constants for the Reactions of Sulfur (3PJ) Atoms in Solution

Abstract: The 248-nm laser flash photolysis of methyl isothiocyanate (MeNCS) was used to generate S( 3 P J ) ground state atoms in acetonitrile solution. The reaction of S( 3 P J ) atoms with the MeNCS precursor produces molecular diatomic sulfur S 2 ( 3 Σ g -) in its ground state, which possesses an absorption at ca. 270 nm. The first-order growth of this absorption was used to monitor the decay kinetics of the sulfur ( 3 P J ) atoms and to measure the rate constants for their reactions with additives. The rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Am. Chem in solution studies of sulfur, 15 chlorine, 16,17 and fluorine atoms. 18 One would expect that complexation and ionization pathways of O( 3 P) may differ in solution compared to the gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Am. Chem in solution studies of sulfur, 15 chlorine, 16,17 and fluorine atoms. 18 One would expect that complexation and ionization pathways of O( 3 P) may differ in solution compared to the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have brought together results on condensed phase O( 3 P) atoms, which address questions about the influence of solvent. Complexes or ions are commonly encountered in solution studies of sulfur, chlorine, , and fluorine atoms . One would expect that complexation and ionization pathways of O( 3 P) may differ in solution compared to the gas phase. , …”
Section: Introductionmentioning
confidence: 99%
“…Laser flash photolysis studies showed a decay of the S 2 signal in the millisecond range. 28 This indicates that the formation of S 8 from the produced S 2 is feasible under the cyclic voltammetric time scale at the investigated low scan rates. Furthermore, the observation, in all cyclic voltammograms at low scan rates for both compounds 1 and 2, of the second peak, corresponding to the second reduction peak of S 8 , is a clear indication that S 8 is indeed formed at the first reduction peak.…”
mentioning
confidence: 65%
“…The yield of complex 9 in the reaction mixture, based on NMR, is ∼65%. Thioisocyanates are sulfur atom transfer reagents that yield the corresponding isocyanides as byproducts. However, a 1 H NMR spectrum of the reaction mixture did not reveal PhNC resonances; presumably the PhNC is consumed in side reactions with complex 1 . Confirming the side reactions, in a test reaction, treating 1 with PhNC in C 6 D 6 results in a complicated mixture of products (NMR spectroscopy) (Figure S18).…”
Section: Resultsmentioning
confidence: 99%